THE IMPLEMENTATION OF THE PROBLEM-BASED LEARNING MODEL IN PRIMARY EDUCATION: AN EMPIRICAL LITERATURE ANALYSIS - Ronald Candy S. Lasaten; Juang Kurniawan (SMART: Journal of Multidisciplinary Educational, 2025)
This study aims to investigate the implementation of the Problem-Based Learning (PBL) model in primary education by analyzing its fidelity, contextual adaptation, and impact on various learning outcomes. Employing a literature review method, this research synthesizes findings from 30 peer-reviewed studies published in the last five years, focusing on the effectiveness and challenges of PBL in elementary school settings. Data were collected through systematic screening of journal databases and analyzed using thematic synthesis to identify recurring themes and research gaps. Results indicate that while PBL is widely reported to enhance students’ cognitive performance, there is limited focus on its impact on affective, social, and metacognitive domains. Furthermore, the findings reveal significant variability in implementation fidelity and a lack of alignment between PBL and national curriculum demands, especially in low-resource classrooms. This study presents a novel contribution by combining implementation fidelity with learner readiness and contextual constraints to offer a comprehensive understanding of PBL in primary education. Unlike previous studies that focused narrowly on test outcomes, this research emphasizes long-term learning transfer and inclusive instructional practices. In conclusion, successful application of PBL requires not only strong teacher preparation but also adaptive frameworks that respond to classroom realities. The study advocates for more holistic evaluation tools and recommends targeted teacher development programs to scale up PBL sustainably across diverse educational systems.